Carbon Pricing and Social Equity in Germany - Gründinger, Wolfgang; Bendling, Lena; Creutzig, Felix; Hagedorn, Gregor; Kemfert, Claudia; Neumärker, Bernhard; Praetorius, Barbara; Tvrtković, Mario (Momentum Quarterly, 2021)
Mitigation of the climate crisis can be married with social equity. Numerous and widely accepted concepts for a sound climate policy framework for Germany with a focus on private households combine climate protection and social cohesion, with net financial benefits for low-income households. Carbon pricing schemes give a striking example. They make carbon emissions more expensive and hence provide market-based steering effects towards a low-carbon economy. Although higher prices can burden consumers, the additional fiscal revenues generated through the carbon pricing can be used to pay a percapita climate bonus to all citizens. This per-capita compensation would result in net benefits for the lower social strata, while preserving the envisioned ecological steering effects. Additionally, the government can reform other fiscal expenses, promote climate-friendly alternatives, and support supplementary social measures. Carbon pricing, as an element of a broad mix of instruments in climate policy, has been subject to intense scientific debate and is hence well-researched. A large body of scientific evidence suggests that carbon pricing can be socially balanced and is long overdue to tackle the climate crisis.